1996
DOI: 10.1016/s0886-3350(96)80216-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subclinical inflammation in phakic eyes with intraocular lenses to correct myopia

Abstract: Our study shows chronic subclinical inflammation between 1 and 2 years after implantation of both IOL types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 17 publications
4
40
1
3
Order By: Relevance
“…Jedoch sind eine Reihe von "morphologischen" Komplikationen beschrieben worden. Dazu gehören u. a. die Dezentrierung der Kunstlinse, akute und chronische Uveitiden, zum Teil einhergehend mit einem chronischen Makulaödem, eine Irisatrophie, eine Verziehung der Pupille, die Entwicklung einer Katarakt, ein induziertes Glaukom, ein progressiver Verlust von Hornhautendothelzellen, vereinzelte Netzhautablösungen und auch Endophthalmitiden [2,3,9,11,13].…”
Section: Schlüsselwörterunclassified
See 1 more Smart Citation
“…Jedoch sind eine Reihe von "morphologischen" Komplikationen beschrieben worden. Dazu gehören u. a. die Dezentrierung der Kunstlinse, akute und chronische Uveitiden, zum Teil einhergehend mit einem chronischen Makulaödem, eine Irisatrophie, eine Verziehung der Pupille, die Entwicklung einer Katarakt, ein induziertes Glaukom, ein progressiver Verlust von Hornhautendothelzellen, vereinzelte Netzhautablösungen und auch Endophthalmitiden [2,3,9,11,13].…”
Section: Schlüsselwörterunclassified
“…Jedoch sind eine Reihe von "morphologischen" Komplikationen beschrieben worden. Dazu gehören u. a. die Dezentrierung der Kunstlinse, akute und chronische Uveitiden, zum Teil einhergehend mit einem chronischen Makulaödem, eine Irisatrophie, eine Verziehung der Pupille, die Entwicklung einer Katarakt, ein induziertes Glaukom, ein progressiver Verlust von Hornhautendothelzellen, vereinzelte Netzhautablösungen und auch Endophthalmitiden [2,3,9,11,13].Bisher sind nur wenige Untersuchungen zu den funktionellen Verände-rungen nach einer solchen Operation durchgeführt worden. Dabei geht es weniger um die eigentliche unkorrigierte oder korrigierte zentrale Sehschärfe als vielmehr um die postoperative Blendempfindlichkeit und das Empfinden von Halos während der Dämmerung oder der Nacht.…”
unclassified
“…Chronic subclinical inflammation has also been observed in phakic eyes with IOLs. 47 It has been suggested that while endothelial cell loss continued over the first three years of follow-up (2%-3% per year), there was a cell increase of 0.1% between three years and four years, suggesting that endothelial remodeling and stability may have occurred. 48 Although multiple factors influence the side effect profile of phakic IOLs, the majority of complications can generally be predicted by the design and location of the phakic IOL within the anterior segment.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the onset of a more or less marked postsurgical inflammatory reaction, the data in literature are very heterogeneous because they cover different surgical techniques and several types of lenses [26][27][28][29]. Some studies have however demonstrated how the onset of cystoid macular edema varies from 6.7% to 42.9% following scleral-fixated IOL implants while it is drastically reduced from 5.7% to 22.2% with 4 ISRN Ophthalmology anterior chamber IOL implants [11,19,[30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%